Karakterisasi Air Kondensat AC sebagai Sumber Air Alternatif - Sri Komala, Puti; Ruslinda, Yenni; Nur, Ansiha; Mardatillah, Regina; Salsabila, Srideva (Dampak, 2025)
This study analyzes the potential to reuse AC condensate water in Andalas University. The research was conducted in the Rectorate Building, the Civil Engineering Department, and the Environmental Engineering Department. AC condensate water sampling was conducted in 8 locations from the Rectorate, Civil Engineering, and Environmental Engineering office buildings. The parameters analyzed were pH, DO, Turbidity, COD, Metals, E.coli, and Total Coliform. Water quality was compared with the Minister of Health Regulation Number 2 of 2023, World Health Organization (WHO) for Drinking Water Quality Standards and Government Regulation Number 22 of 2021 concerning implementing Environmental Protection and Management. The results of water quality testing show that in addition to the parameters of pH, DO, Turbidity, COD, and Metals that have met the quality standards, the levels of iron (Fe), COD, and Total Coliform exceed the quality standards of the Minister of Health Regulation Number 2 of 2023. Used AC water is not recommended for consumption as drinking water. However, condensate AC water can be used for several activities, such as watering plants, cleaning floors and specific areas, and flushing toilets. The AC condensate water characterization results show that iron (Fe), COD, and Total Coliform parameters exceed the quality standards for drinking water requirements. AC condensate water is not recommended for consumption as drinking water without prior treatment. Used AC water can be utilized for several activities, such as watering plants, cleaning the floor, and cleaning the toilet. Keyword: condensate water; office building; potential; water source